STATUS GIZI KURANG BERESIKO TERHADAP USIA MENARCHE PADA SISWI KELAS VI DI SDN 007 RAMBAH KABUPATEN ROKAN HULU - Rahmi Fitria (Jurnal Ilmu Kebidanan, 2021)
Menarche is a sign of the proper functioning of a woman's reproductive organs when having her first menstruation and is common in the age range of 10-16 years. Menarche is influenced by several factors, one of which is nutritional status. According to Noviyanti research (2016) nutrition affects a girl's sexual maturity so that it affects the slowness of menarche. Similarly, research conducted by Munda (2016) that students with overweight nutritional status faster experienced menarche compared to students who have normal nutritional status and underweight. This study aims to find out the relationship of nutritional status to the age of menarche grade VII students in Pesantren Bahrul Ulum. This research method uses descriptive method with cross sectional research design. This research was conducted in SDN 007 Rambah. The sample of this study amounted to 45 respondents. Data collection uses simple correlation and linear regression tests. The results of this study stated that the average nutritional status of grade VII students is 21.60Kg /m2, and the nutritional status of students is at least 16.90 Kg / m2 and the highest nutritional status is 27.60 Kg / m2 with an average age of menarche 12.11 years. The conclusion of this study is that there is no relationship of nutritional status with menarche age in grade VII students in Pesantren Bahrul Ulum with a value of p= 0.036.